The European Union’s enlargement process and cohesion policy: a theoretical appraisal - MacMillan, Catherine (My University, 2002)
The aim of this thesis is to contribute to the continuing discussion about the future of the EU's cohesion policy after the present programming period (2000-2006). It will do this by examining the Agenda 2000 reforms of the Structural Funds in the light of the impending enlargement to the CEECs. In addition to examining the effects that the EU cohesion policy has on reducing regional disparities, the research also takes into account the political functions that cohesion policy plays. Cohesion policy is examined according to Moravcsik's theory of liberal intergovernmentalism in order to determine the importance of intergovernmental bargaining in regional policy formation. While cohesion policy cannot be entirely explained by liberal intergovernmentalism, intergovernmentalism plays an important part. Moreover, cohesion policy has acted as a show of solidarity from the EU's richer regions to the poorer ones, although the effect on reducing regional disparities has been relatively limited in most cases. Therefore, cohesion policy is also likely to play an important part in a smooth enlargement to the CEECs. Given this importance, the thesis concludes that the Agenda 2000 reforms are insufficient in several respects vis a vis the extension of cohesion policy to the CEECs. The thesis proposes, therefore, that a new fund should be set up tailored to the special needs of the candidate countries.

Bu tezin amacı, AB'nin mevcut planlanmış dönem (2000-2006) sonrası ''uyum politikası''nın geleceği hakkında sürüp giden tartışmaya katkı sağlamaktır. Bunu da Orta ve Doğu Avrupa ülkelerine yönelik olası genişlemenin ışığı altında, Ajanda 2000'in yapısal fon reformlarını sorgulayarak yapacaktır. AB uyum politikasının bölgesel farklılıkların azaltılması üzerinde sahip olduğu etkilerin araştırılmasına ek olarak, çalışmada uyum politikasının oynadığı siyasi fonksiyonlar da dikkate alınmaktadır. Uyum politikası, bölgesel politika oluşturmada hükümetlerarası görüşmelerin önemini belirlemek için, Moravcsik'in liberal intergovermentalist teorisine göre incelenmektedir. Uyum politikası liberal intergovermentalism ile tam olarak açıklanamasa da, uyum politikası çerçevesinde intergovermentalism önemli bir rol oynamaktadır. Bununla beraber, bölgesel farklılıkların azaltılması üzerindeki etkisi birçok durumda göreceli olarak sınırlı kalsa bile, uyum politikası AB'nin zengin bölgelerinden daha fakir bölgelerine bir birlik, bütünlük gösterisi olarak hareket etmektedir. Dolayısıyla, uyum politikası Orta ve Doğu Avrupa ülkelerine yönelik sorunsuz bir genişlemede önemli bir rol oynayacaktır. Bu önem gözönünde tutulduğunda; tez, Ajanda 2000 reformlarının uyum politikasının Orta ve Doğu Avrupa ülkelerine doğru genişlemesi sürecinde birkaç açıdan yetersiz kaldığı sonucuna varmaktadır. Dolayısıyla, tez aday ülkelerin özel ihtiyaçlarına yönelik olarak değiştirilmiş yeni bir fon inşa edilmesi gerektiğini önermektedir.
Keywords: Avrupa Birliği